Sistem Monitoring Dan Kontroling Kualitas Air Tambak Udang Vannamei Berbasis Arduino Menggunakan Teknologi Internet Of Things - Setiawan, Nuris Dwi; Dianta, Indra Ava (LPPM UNIKA Santo Thomas Medan, 2020)
Vannamei shrimp is a variety of shrimp that is very sensitive to changes in water quality, growth and life of vannamei shrimp which are directly affected by changes in temperature, salt content, dissolved oxygen, and pH (Hydrogen Potential) content in water. So far, vannamei shrimp cultivators know the quality of water by taking pond water samples with a certain period of time, uncertain natural conditions can make pond water quality change drastically if not maintained can inhibit growth or result in shrimp death.Making a monitoring system and controlling the quality of shrimp pond water using a water temperature sensor, salinity sensor, DO sensor and pH sensor installed on the Arduino Mega 2560 device, NodeMCU is used to receive and send data wirelessly, the system uses programming language c. This tool can be used to start the waterwheel automatically if it is within a certain threshold to maintain the temperature and dissolved oxygen in the pool water based on the value obtained from the sensor. The monitoring results obtained will be displayed to the user in real time through the interface and will be stored in the form of a text file on the storage media.